Answer:
y-1=2(x+3)
y-1=2x+6
y=2x+6+1
y=2x+7
x - y = 8
Answer:
C. (5, -3)
Step-by-step explanation:
4x + 3y = 11
x - y = 8 (multiply by 3) --> 3x - 3y = 24
4x + 3y = 11
3x - 3y = 24
---------------------add
7x = 35
x = 5
5 - y = 8
y = 5 - 8
y = -3
(5, -3)
Answer:
C. (5, -3)
Step-by-step explanation:
Rewrite the first equation.
Multiply the second equation by 3 and write it under the first equation.
4x + 3y = 11
3x - 3y = 24
Now add the equations.
7x = 35
Divide both sides by 7.
x = 5
Substitute 5 for x in the original first equation:
4(5) + 3y = 11
20 + 3y = 11
3y = -9
y = -3
Solution: (5, -3)
A. Prove that QR ≅ QR by reflexive property
Nikki is going to use SSS Property, which is Side, Side, Side. This means that, given two pairs of sides are congruent, you will have to find out the last side, which is the same side. This means that it is congruent with itself (since both triangles share the same side), and uses the reflexive property.
hope this helps
Answer: A is the correct answer
Step-by-step explanation: